THE EFFECT OF FOOD, FUN, AND FASHION FOR MUSLIM - Zubarita, Fatma Reza (Journal of Islamic Law Studies, 2021)
In era modern, many person forget how to be a true Muslim. When modernization come, Western people use their logic for influence Muslim to follow what they want. It’s about Fun, Food, and Fash- ion. Many muslim have followed it, and sometimes make them to be a comsumtive person. Not just it. It is still many effect of it. Muslim start to leave science of Al-Qur’an and hadith. They want a happy and enjoy life. This is one of effect also, if current teenagers loss a moral and good character. So, Muslim must be resuscitated to be true Muslim by Role of Religion. How to make Muslim for love Alquran and Hadith. Its is for guidelines and principle.